Sugar Sweetened Beverages Labels and SSB Purchase among Adults : Narative Review - Larasati, Adisti Qamahadlina (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Sugar-sweetened beverages (SSBs) are beverages to which sugar is added. SSBs are low in nutritional value, and have been associated with various health risks, such as increased incidence of obesity, cardiovascular disease, diabetes mellitus, and dental caries. Labeling on SSBs was one of potential strategies used to reduce the purchase and intake of SSB. Objective: This review aims to summarize findings from previous studies on the effect of labeling on SSBs in relation to purchasing of SSBs among adults. Methods: A literature search was conducted through Google Scholar and PubMed using these keywords (“nutrition label” OR “warning label” OR “food label” OR “health label”) AND (“sugar sweetened beverage” OR “SSB” OR “sugary drink”) AND (“behavior” OR “purchase”) AND (“adult”). Articles published in the range of 10 years (2015-2025) were included. Results: The search found 10 articles that met the inclusion and exclusion criterias. The labels used in the studies were primarily text health warning labels and graphic health warning labels. Most studies reported that labels used in SSB products reduced consumers’ intention to choose SSBs. Conclusion: SSB labeling, whether in text or image form, has the potential to reduce consumers’ purchasing intentions of sugar-sweetened beverages.